Institutional change in Turkey : the impact of European Union reforms on human rights and policing - Piran, Leila; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2013)
How do state institutions reform themselves in the face of outside pressures? This study undertakes an in-depth analysis of the institutional and human rights reform process within the Turkish National Police, which faces pressure from the EU as part of Turkey's EU membership process, and examines the challenges and consequences of the process.
Keywords: Political science; European Union; Middle East -- Politics and government; International relations; Human rights; Police; Social justice; Political Science and International Relations; Middle Eastern Politics; International Relations; European Union Politics; Social Justice, Equality and Human Rights; Policing; Human Rights